Fracture in the Elderly Multidisciplinary Rehabilitation (FEMuR): study protocol for a phase II randomised feasibility study of a multidisciplinary rehabilitation package following hip fracture - Williams, Nefyn H.; Roberts, Jessica L.; Ud Din, Nafees; Totton, Nicola; Charles, Joanna M.; Hawkes, Claire A.; Morrison, Val; Zoe, Hoare; Williams, Michelle; Pritchard, Aaron W.; Alexander, Swapna; Lemmey, Andrew; et al. (BMJ Publishing Group Ltd, 2016)
Objective: To conduct a rigorous feasibility study for a future definitive parallel-group randomised controlled trial (RCT) and economic evaluation of an enhanced rehabilitation package for hip fracture.